The asymmetric evolution of the social case-law of the Court of Justice: new challenges in the context of the European pillar of social rights - Jimena Quesada, Luis (UNIO – EU Law Journal, 2019)
The author highlights the paradoxical evolution of CJEU’s case-law in the field of social rights and how in the past, it has played a praetorian role in a context of implied powers and modest EU primary legal provisions whereas now, it is showing clear self-restraint under explicit competences and an evolved EU primary law [including the Charter of Fundamental Rights (CFREU)]. From this perspective, the author proposes the opening of the CJEU to the new framework of the European Pillar of Social Rights, as part of the broader Turin process for the European Social Charter, through positive judicial willingness (by taking into account the synergies between the EU and the Council of Europe – including the case-law from the European Committee of Social Rights).